2003
DOI: 10.1017/s0033291702006943
|View full text |Cite
|
Sign up to set email alerts
|

Psychological autopsy studies of suicide: a systematic review

Abstract: The results indicated that mental disorder was the most strongly associated variable of those that have been studied. Further studies should focus on specific disorders and psychosocial factors. Suicide prevention strategies may be most effective if focused on the treatment of mental disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

58
1,117
13
72

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,771 publications
(1,260 citation statements)
references
References 130 publications
58
1,117
13
72
Order By: Relevance
“…Critical voices have been raised against diagnostic practices and the potential adverse effects of psychiatric medication (Gøtzsche, 2013; Whitaker, 2010), and several authors have questioned the overreliance on biomedical models with regard to how we understand and manage suicidality (Cutcliffe & Santos, 2012; Hjelmeland, Dieserud, Dyregrov, Knizek, & Rasmussen, 2014; Marsh, 2016; Webb, 2010). Even the assumption that 90% of all suicides are associated with mental disorders (Cavanagh, Carson, Sharpe, & Lawrie, 2003) is strongly challenged by researchers who argue that there is no valid evidence for this 90% statistic (Hjelmeland, Dieserud, Dyregrov, Knizek, & Leenaars, 2012). However, psychiatry continues to be heavily influenced by a biomedical ideology that in turn affects how mental health workers understand suicidality and approach suicidal patients (Hagen et al, 2017; Michel et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Critical voices have been raised against diagnostic practices and the potential adverse effects of psychiatric medication (Gøtzsche, 2013; Whitaker, 2010), and several authors have questioned the overreliance on biomedical models with regard to how we understand and manage suicidality (Cutcliffe & Santos, 2012; Hjelmeland, Dieserud, Dyregrov, Knizek, & Rasmussen, 2014; Marsh, 2016; Webb, 2010). Even the assumption that 90% of all suicides are associated with mental disorders (Cavanagh, Carson, Sharpe, & Lawrie, 2003) is strongly challenged by researchers who argue that there is no valid evidence for this 90% statistic (Hjelmeland, Dieserud, Dyregrov, Knizek, & Leenaars, 2012). However, psychiatry continues to be heavily influenced by a biomedical ideology that in turn affects how mental health workers understand suicidality and approach suicidal patients (Hagen et al, 2017; Michel et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It remains unclear, however, how to isolate this specific association from the association between non-psychotic psychopathology and suicidal ideation and behaviour, since non-psychotic psychopathology is strongly connected to both PE (DeVylder et al, 2014;Guloksuz et al, 2015;Jeppesen et al, 2015;Kelleher et al, 2012b;Van Os et al, 2000), and suicidal behaviour (Cavanagh et al, 2003;ten Have et al, 2009;Ten Have et al, 2013). Suicidality comprises various phenomena on a continuum ranging from suicidal ideation, suicide plans and suicide attempts to completed suicide (Nock, 2010;Sveticic and De Leo, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Even though the mechanisms underlying suicidal behaviour remain poorly understood, research has shown that it is likely determined by a complex interplay of biological, psychological, environmental and cultural factors (O'Connor et al, 2011;World Health Organization, 2014). Mental disorders are an important risk factor for suicidal behaviour (Bostwick and Pankratz, 2000;Nordentoft et al, 2011;Palmer et al, 2005): of the individuals who committed suicide, 91% had a mental disorder, most commonly a depressive disorder, substance abuse or schizophrenia (Cavanagh et al, 2003;ten Have et al, 2009;Ten Have et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, exposure to incidents of community violence can lead directly or indirectly to psychological distress, poor mental health outcomes such anxiety and depression, behavioral problems, and substance misuse (see for example 5 ), each of which are major risk factors for suicide. 6,7 Previous research among adolescents has shown that exposure to violence can increase suicidality. [8][9][10][11] However, these studies were generally limited to small samples, utilized self-reported measures of violence exposure and suicide-related outcomes, and assessed suicidal ideation or attempt rather than completed suicides.…”
Section: Introductionmentioning
confidence: 99%
“…12 For example, those already at high risk due to psychiatric disorder 7 or poor physical health 13 experience dually increased risk when confronted with distressing life events. 14 Identification of the groups most affected by community violenceinduced conditions is important to better inform priority setting and to better understand the relationship between community violence and health.…”
Section: Introductionmentioning
confidence: 99%